(untitled) (Fiep Bulletin - online, 2014)
This research talks about the experiences of residents physical education teachers, to describe the possible meanings attributed by patients with mental disorders face to dance activities . The issue arises from the constant demands of patients admitted to the psychiatric clinic of the Clinic Hospital Dr. Alberto Lima (HCAL) for dance activities developed by physical education teachers coming from Multidisciplinary Residency Program in Public Health with emphasis on line training Attention to Mental Health, Federal University of Amapá and this body practice is suggested therapeutic plan of patients. We register this qualitative study, descriptive, had as subjects the patients of psychiatric service in the HCAL with different diagnosis of mental disorders. For the study, we used the months of June and August 2013, with the number of participants varied each week, due to the clinical, hospital admissions, readmissions and hospital discharges. It is understood that the dance activities bring different interpretations to patients with mental disorders; however, there is a consensus that the proposed benefits are great for practice, they’re organic or psychological. The idea of ??having to dance as a possible therapeutic action in the activities of mental health service highlights the importance of the presence and action of physical education professionals in the multidisciplinary team of mental health, it is based on the model of care focused on non-medical action, but new perspectives on care services and health promotion .